Al-Cu-RE series rare earth aluminum alloy and preparation method thereof, and heat-resistant cable
By adding Cu, Mg, Si, In, Sn and RE to the aluminum matrix, the Al-Cu-RE-based rare earth aluminum alloy is formed, which solves the problems of high cost and process complexity of existing aluminum alloys for heat-resistant cables, and achieves high comprehensive performance and low cost effects.
Patent Information
- Application Number
- CN202311397641.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-10-26
AI Technical Summary
The existing aluminum alloy for heat-resistant cables has problems with high cost and process complexity in improving comprehensive performance, and the addition of too many elements has failed to effectively reduce costs and complexity.
Al-Cu-RE-based rare earth aluminum alloy is used to ensure the interaction and influence between elements by adding fewer types of low-priced elements, such as Cu, Mg, Si, In, Sn and RE, to the aluminum matrix, so as to reduce solid solubility and improve conductive and mechanical properties.
On the basis of maintaining low cost and low process complexity, the comprehensive performance of Al-Cu-RE rare earth aluminum alloys is significantly improved, including mechanical properties, heat resistance, corrosion resistance and electrical conductivity, and is at a low cost.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum alloys, and in particular to an Al-Cu-RE series rare earth aluminum alloy, a preparation method of the Al-Cu-RE series rare earth aluminum alloy, and a heat-resistant cable using the Al-Cu-RE series rare earth aluminum alloy. Background Art
[0002] At present, my country's aluminum alloy conductor materials are mainly divided into the following three categories: high-conductivity aluminum alloy conductor materials, high-strength and high-conductivity aluminum alloy materials, and high-strength and high-conductivity heat-resistant aluminum alloy conductor materials. High-conductivity aluminum alloy conductor materials mainly include Al-Fe aluminum alloy, Al-Cu aluminum alloy, and electrical aluminum (such as electrical aluminum 1350 or electrical aluminum 1B90, etc.). High-conductivity aluminum alloy conductor materials belong to soft wire aluminum alloys. The mechanical properties and creep resistance are generally low, while the conductivity is high (reaching 61-63% IACS), and are generally used at the low-voltage end. High-strength and high-conductivity aluminum alloy materials mainly include Al-Mg-Si aluminum alloys. High-strength and high-conductivity aluminum alloy materials have good mechanical properties and corrosion resistance, but low conductivity (generally less than 58% IACS), and are mainly used for overhead lines, such as in ultra-high voltage and large-span transmission lines such as the Yangtze River and Han River. High-strength and high-conductivity heat-resistant aluminum alloy conductor materials mainly include Al-Zr-RE aluminum alloys. High-strength, high-conductivity, heat-resistant aluminum alloy conductor material has good conductivity, mechanical properties and heat resistance, and can be used in high temperature environments below 150°C.
[0003] The applicant established an aluminum alloy new material research and development department in 2021, and conducted research and development on aluminum alloys for heat-resistant cables, such as Al-Cu aluminum alloys. The study found that as the requirements for the performance of aluminum alloys for heat-resistant cables become higher and higher, in order to obtain aluminum alloys for heat-resistant cables with good comprehensive performance, a variety of elements with different functions are usually added to aluminum. For example, in patent CN102978448B, in which Lin Zemin is the inventor, 36 elements are added to aluminum. The addition of too many elements will increase the cost (the total content of elements is too high and there is no lack of expensive elements added) and increase the complexity of the process. Moreover, the addition of too many elements means that the existing preparation process of aluminum alloys for heat-resistant cables does not improve the comprehensive performance of aluminum alloys for heat-resistant cables in a targeted manner on the basis of reducing costs and process complexity. To this end, the applicant has continuously innovated experiments and proposed a new invention of Al-Cu-RE rare earth aluminum alloys for heat-resistant cables with excellent comprehensive performance, which can be obtained by using only a small number of low-priced elements on the basis of maintaining low cost and low process complexity. Summary of the invention
[0004] In view of the above-mentioned defects of the prior art, the present invention provides an Al-Cu-RE series rare earth aluminum alloy, which aims to obtain an Al-Cu-RE series rare earth aluminum alloy for heat-resistant cables with excellent comprehensive properties (especially mechanical properties, heat resistance, corrosion resistance, and electrical conductivity) by using only a small number of low-priced elements while maintaining low cost and low process complexity.
[0005] The present invention provides an Al-Cu-RE series rare earth aluminum alloy, which contains Al. The Al-Cu-RE series rare earth aluminum alloy also contains 0.01-0.6% by mass of Cu, 0.001-0.2% by mass of RE, 0-0.7% by mass of Mg, 0-0.3% by mass of Si, 0-0.2% by mass of In, and 0-0.3% by mass of Sn.
[0006] Furthermore, at least one of the following conditions is met:
[0007] The mass ratio of Mg to Si is 0.2-40:1;
[0008] The mass ratio of Cu to Si is 0.5-30:1;
[0009] The mass ratio of Mg to In is 0.3-40:1;
[0010] The mass ratio of Cu to In is 0.3-40:1;
[0011] The mass ratio of Mg, Sn, and Si is 1-20:0.5-5:1;
[0012] RE is at least one of La, Ce, Pr, Nd, Er, Sm, Y, and Gd.
[0013] Furthermore, at least one of the following conditions is met:
[0014] The Al-Cu-RE rare earth aluminum alloy also contains Sb with a mass percentage of 0-0.5%;
[0015] The Al-Cu-RE series rare earth aluminum alloy also contains Sr with a mass percentage of 0-0.2%;
[0016] The Al-Cu-RE rare earth aluminum alloy also contains 0-0.3% by mass of Zn;
[0017] The Al-Cu-RE rare earth aluminum alloy also contains 0-0.1% Be by mass;
[0018] The Al-Cu-RE rare earth aluminum alloy also contains Bi in a mass percentage content of 0-0.3%;
[0019] The Al-Cu-RE rare earth aluminum alloy also contains 0-0.3% by mass of Mo;
[0020] The Al-Cu-RE rare earth aluminum alloy also contains Cd in an amount of 0-0.3% by mass;
[0021] The Al-Cu-RE rare earth aluminum alloy also contains Co in a mass percentage content of 0-0.8%;
[0022] The Al-Cu-RE rare earth aluminum alloy further contains Ca in a mass percentage content of 0-0.5%;
[0023] The Al-Cu-RE rare earth aluminum alloy further contains Ge in a mass percentage content of 0-0.3%.
[0024] Furthermore, the Al-Cu-RE series rare earth aluminum alloy also contains 0-0.3% Fe by mass, wherein the mass ratio of Mg to Fe is 0.2-20:1, and the mass ratio of Si to Fe is 0.1-5:1.
[0025] Furthermore, the Al-Cu-RE series rare earth aluminum alloy also contains 0-0.1% by mass of B, wherein the mass ratio of In to B is 0.1-10:1.
[0026] Furthermore, the Al-Cu-RE rare earth aluminum alloy also contains 0-0.3% by mass of Sc and 0-0.3% by mass of Zr, the mass ratio of Mg to Sc is 0.2-30:1, the mass ratio of Cu to Sc is 1-30:1, and the mass ratio of Sc to Zr is 0.5-2.5:1.
[0027] Furthermore, the Al-Cu-RE rare earth aluminum alloy also contains 0-0.1% by mass of B, 0-0.3% by mass of Fe, and 0-0.3% by mass of Sc, wherein the mass ratio of Sc to Fe is 0.01-10:1, and the mass ratio of Sc, In, and B is 0.1-15:0.1-10:1.
[0028] The present invention also provides a method for preparing an Al-Cu-RE series rare earth aluminum alloy, comprising the following steps:
[0029] The aluminum source is subjected to a first heating treatment to obtain aluminum liquid;
[0030] Adding Cu, Mg, Si, RE, In, and Sn to the aluminum liquid, performing a second heating treatment, and obtaining an alloy liquid;
[0031] Refining and slagging the alloy liquid, and testing its composition and content;
[0032] After the composition and content are tested to be qualified, the alloy liquid after the refining treatment and slag removal treatment is subjected to continuous casting, continuous rolling and drawing treatment to obtain aluminum alloy wire; and
[0033] The aluminum alloy wire is subjected to aging treatment to obtain an Al-Cu-RE series rare earth aluminum alloy, wherein the Al-Cu-RE series rare earth aluminum alloy contains Al, and further contains 0.01-0.6% by mass of Cu, 0.001-0.2% by mass of RE, 0-0.7% by mass of Mg, 0-0.3% by mass of Si, 0-0.2% by mass of In, and 0-0.3% by mass of Sn.
[0034] Furthermore, at least one of the following conditions is met:
[0035] The preparation method of the Al-Cu-RE series rare earth aluminum alloy further comprises the step of adding at least one of Sb, Sr, Zn, B, Be, Bi, Mo, Cd, Fe, Ca, Ge, Zr, Sc and Co to the aluminum liquid;
[0036] The aging treatment is a bipolar aging treatment, which includes the following steps: firstly performing a low-temperature aging treatment at a temperature of 100-150° C. for a time of 1-150 h; and then performing a high-temperature aging treatment at a temperature of 150-250° C. for a time of 1-100 h.
[0037] The present invention also provides a heat-resistant cable, which comprises a wire core and an insulating layer covering the wire core, wherein the material of the wire core is the Al-Cu-RE series rare earth aluminum alloy.
[0038] In the technical solution of the present invention, the Al-Cu-RE rare earth aluminum alloy contains 0.01-0.6% Cu by mass, 0.001-0.2% RE by mass, 0-0.7% Mg by mass, 0-0.3% Si by mass, 0-0.2% In by mass, and 0-0.3% Sn by mass. When the above elements are added to the aluminum matrix alone, the improvement of the electrical conductivity and mechanical properties of aluminum is limited, and even has a negative effect on the electrical conductivity and mechanical properties of aluminum. The present invention adds the above elements to the aluminum matrix together, and the above elements interact and influence each other, which can reduce the solid solubility of each other in the aluminum matrix, thereby reducing the adverse effects of certain elements on electrical conductivity and improving electrical conductivity. The elements will also dissolve into other precipitated phases and second phases to form strengthening phases, thereby significantly improving the comprehensive performance of aluminum alloys. The Al-Cu-RE rare earth aluminum alloy uses a small number of elements and is inexpensive. Although RE and Sc are slightly more expensive, their use is small, which has little impact on the cost of the Al-Cu-RE rare earth aluminum alloy. In addition, RE and Sc have mechanical properties and electrical conductivity that cannot be matched by other elements. The mutual cooperation of each element can also promote the precipitation volume fraction of the strengthening phase to reduce the total amount of elements added to the aluminum matrix. Generally, in a soft heat-resistant cable, the amount of alloying elements added is inversely proportional to the electrical conductivity and elongation, and is proportional to the tensile strength and yield strength. In the soft state, to ensure that the electrical conductivity reaches the national standard value (greater than 61% IACS), the total amount of elements added to the aluminum alloy for cables does not exceed 1.0wt%; to ensure that the tensile strength is greater than 185MPa, the total amount of elements added to the aluminum alloy for cables generally exceeds 1.0wt%, however, the electrical conductivity will definitely be lower than the national standard value (greater than 61% IACS); while the present invention, under the premise of ensuring mechanical properties and electrical conductivity, when the total amount of elements added to the aluminum alloy is less than 1.0wt%, better comprehensive performance can be achieved (specifically, the tensile strength of the Al-Cu-RE rare earth aluminum alloy is greater than the tensile strength of the hard alloy, the elongation of the Al-Cu-RE rare earth aluminum alloy is greater than the elongation of the soft alloy, and the electrical conductivity is greater than 61% IACS), thereby reducing the cost of the Al-Cu-RE rare earth aluminum alloy. In summary, the present invention can obtain Al-Cu-RE rare earth aluminum alloy for heat-resistant cables with excellent comprehensive properties (especially mechanical properties, heat resistance, corrosion resistance, and electrical conductivity) by using only a small number of low-priced elements while maintaining low cost and low process complexity. DETAILED DESCRIPTION
[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] An embodiment of the present invention provides an Al-Cu-RE rare earth aluminum alloy, which contains 0.01-0.6% Cu by mass, 0.001-0.2% RE by mass, 0-0.7% Mg by mass, 0-0.3% Si by mass, 0-0.2% In by mass, 0-0.3% Sn by mass, Al and unavoidable impurities.
[0041] In one embodiment, the mass percentage content of Cu may be 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, or 0.6%; the mass percentage content of Mg may be 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, or 0.6%. 33%, 0.34%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, or 0.7%; the mass percentage content of Si can be 0.001%, 0.005%, 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.21%, 0.25%, or 0.3%; the mass percentage content of RE can be 0.001%, 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05% , 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, or 0.2%; the mass percentage content of In can be 0.001%, 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0. The mass percentage content of Sn can be 0.001%, 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.2%, 0.25%, or 0.3%.
[0042] The mass ratio of Mg, Sn and Si is 1-20:0.5-5:1. Specifically, the mass ratio of Mg, Sn and Si is 1:0.5:1, 1:1:1, 1:1.5:1, 1:2:1, 1:2.5:1, 1:3:1, 1:4:1, 1:4.5:1, 1:5:1, 5:0.5:1, 5:1:1, 5:1.5:1, 5:2:1, 5:2.5:1, 5:3:1, 5:4:1, 5:4.5:1, 5:5:1, 10:0.5:1, 10:1:1, 10:1.5:1, 10:2:1, 10:2 .5:1, 10:3:1, 10:4:1, 10:4.5:1, 10:5:1, 15:0.5:1, 15:1:1, 15:1.5:1, 15:2:1, 15:2.5:1, 15:3:1, 15:4:1, 15:4.5:1, 15:5:1, 20:0.5:1, 20:1:1, 20:1.5:1, 20:2:1, 20:2.5:1, 20:3:1, 20:4:1, 20:4.5:1, or 20:5:1.
[0043] The mass ratio of Mg to Si is 0.2-40: 1. Specifically, the mass ratio of Mg to Si is 0.2: 1, 0.5: 1, 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, 20: 1, 30: 1, or 40: 1. Within the range of the mass ratio, as the mass ratio of Mg / Si increases, the conductive strength gradually increases.
[0044] The mass ratio of Cu to Si may be 0.5-30: 1. Specifically, the mass ratio of Cu to Si is 0.5: 1, 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, 20: 1, 25: 1, 30: 1, 35: 1, or 40: 1. Within the range of this mass ratio, as the mass ratio of Cu / Si increases, the tensile strength gradually increases.
[0045] The mass ratio of Mg to In is 0.3-40: 1. Specifically, the mass ratio of Mg to In is 0.3: 1, 0.5: 1, 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, 20: 1, 25: 1, 30: 1, 35: 1, or 40: 1. Within the range of the mass ratio, as the mass ratio of Mg / In increases, the conductive strength gradually increases.
[0046] The mass ratio of Cu to In is 0.3-40:1. Specifically, the mass ratio of Cu to In is 0.3:1, 0.5:1, 1:
[0047] 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, 20: 1, 25: 1, 30: 1, 35: 1, or 40: 1. Within the range of this mass ratio, as the mass ratio of Cu / In increases, the tensile strength gradually increases.
[0048] RE is at least one of La, Ce, Pr, Nd, Er, Sm, Y, and Gd.
[0049] The Al-Cu-RE rare earth aluminum alloy further contains 0-0.5% by mass of Sb, which may be 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, or 0.5% by mass.
[0050] The Al-Cu-RE rare earth aluminum alloy further contains 0-0.2% Sr by mass. The Sr by mass content may be 0.001%, 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, or 0.2%.
[0051] The Al-Cu-RE rare earth aluminum alloy further contains 0-0.3% by mass of Zn, which may be 0.001%, 0.01%, 0.04%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, or 0.3% by mass.
[0052] The Al-Cu-RE rare earth aluminum alloy further contains 0-0.1% Be by mass. The Be by mass content may be 0.001%, 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, or 0.1%.
[0053] The Al-Cu-RE rare earth aluminum alloy further contains 0-0.3% by mass of Bi, which may be 0.001%, 0.01%, 0.04%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, or 0.3% by mass.
[0054] The Al-Cu-RE rare earth aluminum alloy further contains 0-0.3% by mass of Mo. The mass percentage of Mo can be specifically 0.001%, 0.01%, 0.04%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, or 0.3%.
[0055] The Al-Cu-RE rare earth aluminum alloy further contains 0-0.3% by mass of Cd, which may be 0.001%, 0.01%, 0.04%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, or 0.3% by mass.
[0056] The Al-Cu-RE rare earth aluminum alloy further contains 0-0.8% by mass of Co. The mass percentage of Co may specifically be 0.01%, 0.05%, 0.1%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, or 0.8%.
[0057] The Al-Cu-RE rare earth aluminum alloy further contains 0-0.5% by mass of Ca, which may be 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, or 0.5% by mass.
[0058] The Al-Cu-RE rare earth aluminum alloy further contains 0-0.3% by mass of Ge, which may be 0.001%, 0.01%, 0.04%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, or 0.3% by mass.
[0059] The Al-Cu-RE rare earth aluminum alloy further contains 0-0.3% Fe by mass. The Fe by mass content may be 0.001%, 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.2%, 0.25%, or 0.3%.
[0060] The mass ratio of Mg to Fe can be 0.2-20:1, specifically 0.2:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, or 20:1.
[0061] The mass ratio of Si to Fe can be 0.1-5:1, specifically 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 2:1, 3:1, 4:1, or 5:1.
[0062] The Al-Cu-RE rare earth aluminum alloy further contains Sc in a mass percentage content of 0-0.3%. The mass percentage content of Sc can specifically be 0.001%, 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, or 0.2%. The mass percentage content of Sn can specifically be 0.001%, 0.01%, 0.04%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, or 0.3%.
[0063] The Al-Cu-RE rare earth aluminum alloy further contains 0-0.3% by mass of Zr, which may be 0.001%, 0.01%, 0.04%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, or 0.3% by mass.
[0064] The mass ratio of Sc to Fe can be 0.1-10:1, specifically 0.1:1, 0.2:1, 0.5:1, 1:1, 2:
[0065] 1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1.
[0066] The mass ratio of Mg to Sc is 0.1-20: 1. Specifically, the mass ratio of Mg to Sc is 0.1: 1, 0.2: 1, 0.5: 1, 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, or 20: 1. Within the range of the mass ratio, as the mass ratio of Mg / Sc increases, the conductive strength gradually increases.
[0067] The mass ratio of Cu to Sc may be 1-30: 1. Specifically, the mass ratio of Cu to Sc is 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, 20: 1, 25: 1, or 30: 1. Within the range of this mass ratio, as the mass ratio of Cu / Sc increases, the tensile strength gradually increases.
[0068] The mass ratio of Sc to Zr is 0.5-2.5:1, and can be specifically 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 2:1, or 2.5:1.
[0069] The Al-Cu-RE rare earth aluminum alloy further contains 0-0.1% by mass of B. The mass percentage of B can be specifically 0.001%, 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, or 0.1%.
[0070] The mass ratio of In to B is 0.1-10:1, for example, 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1.
[0071] The mass ratio of Sc, In, and B is 0.1-15:0.1-10:1, preferably 1-10:1-5:1. The mass ratio of Sc, In, and B can be specifically 0.1:0.1:1, 0.5:0.1:1, 1:0.1:1, 5:0.1:1, 10:0.1:1, 15:0.1:1, 0.1:1:1, 0.5:1:1, 1:1:1, 5:1:1, 10:1:1, 15:1:1, 0.1:5:1, 0.5:5:1, 1:5:1, 5:5:1, 10:5:1, 15:5:1, 0.1:10:1, 0.5:10:1, 1:10:1, 5:10:1, 10:10:1, or 15:10:1.
[0072] The mass percentage content of the impurities is no more than 0.15%, and the mass percentage content of a single impurity is less than 0.05%.
[0073] In the technical solution of the present invention, the Al-Cu-RE rare earth aluminum alloy contains 0.01-0.6% Cu by mass, 0.001-0.2% RE by mass, 0-0.7% Mg by mass, 0-0.3% Si by mass, 0-0.2% In by mass, and 0-0.3% Sn by mass. When the above elements are added to the aluminum matrix alone, the improvement of the electrical conductivity and mechanical properties of aluminum is limited, and even has a negative effect on the electrical conductivity and mechanical properties of aluminum. The present invention adds the above elements to the aluminum matrix together, and the above elements interact and influence each other, which can reduce the solid solubility of each other in the aluminum matrix, thereby reducing the adverse effects of certain elements on electrical conductivity and improving electrical conductivity. The elements will also dissolve into other precipitated phases and second phases to form strengthening phases, thereby significantly improving the comprehensive performance of aluminum alloys. The Al-Cu-RE rare earth aluminum alloy uses a small number of elements and is inexpensive. Although RE and Sc are slightly more expensive, their use is small, which has little impact on the cost of the Al-Cu-RE rare earth aluminum alloy. In addition, RE and Sc have mechanical properties and electrical conductivity that cannot be matched by other elements. The mutual cooperation of each element can also promote the precipitation volume fraction of the strengthening phase to reduce the total amount of elements added to the aluminum matrix. Generally, in a soft heat-resistant cable, the amount of alloying elements added is inversely proportional to the electrical conductivity and elongation, and is proportional to the tensile strength and yield strength. In the soft state, to ensure that the electrical conductivity reaches the national standard value (greater than 61% IACS), the total amount of elements added to the aluminum alloy for cables does not exceed 1.0wt%; to ensure that the tensile strength is greater than 185MPa, the total amount of elements added to the aluminum alloy for cables generally exceeds 1.0wt%, however, the electrical conductivity will definitely be lower than the national standard value (greater than 61% IACS); while the present invention, under the premise of ensuring mechanical properties and electrical conductivity, when the total amount of elements added to the aluminum alloy is less than 1.0wt%, better comprehensive performance can be achieved (specifically, the tensile strength of the Al-Cu-RE rare earth aluminum alloy is greater than the tensile strength of the hard alloy, the elongation of the Al-Cu-RE rare earth aluminum alloy is greater than the elongation of the soft alloy, and the electrical conductivity is greater than 61% IACS), thereby reducing the cost of the Al-Cu-RE rare earth aluminum alloy. In summary, the present invention can obtain Al-Cu-RE rare earth aluminum alloy for heat-resistant cables with excellent comprehensive properties (especially mechanical properties, heat resistance, corrosion resistance, and electrical conductivity) by using only a small number of low-priced elements while maintaining low cost and low process complexity.
[0074] Elements such as Mg, Si, Ti, Mn, V, and Cr are the main harmful impurity elements that affect the electrical conductivity of aluminum. It is necessary to reduce the amount of addition or treat them to reduce their influence on the electrical conductivity. In the technical solution of the present invention, the amount of Mg, Si, Cu, In, and Sn added (which can reach 0.7%, 0.3%, 0.6%, 0.2%, and 0.3%, respectively) can be greater than the amount of Mg, Si, Cu, In, and Sn added in the prior art (which can reach 0.3%, 0.08%, 0.25%, 0.1%, and 0.08%, respectively), so that the Al-Cu-RE series rare earth aluminum alloy has better comprehensive properties, especially mechanical properties, heat resistance, corrosion resistance, and electrical conductivity. The specific reasons are as follows:
[0075] (1) The amount of Si added can reach 0.3%, which can be greater than the amount of Si added in the prior art (Si exists in the aluminum matrix in a solid solution state, and its lattice constant is very different from that of Al, which can easily cause large lattice distortion and have a great influence on the electrical conductivity of aluminum. It is the main impurity element affecting the electrical conductivity of aluminum. Therefore, the amount of Si added in the prior art is relatively small, usually not more than 0.08%). Si can react with Al and Fe to form (Al, Fe, Si) intermetallic compounds (it can be understood that the aluminum source usually contains Fe impurities. When there is no Fe impurity in the aluminum source used or Fe is not added to the aluminum matrix, Si will naturally not react with Fe to form iron-containing compounds). The amount of Mg added is sufficient, so that a large amount of Si can react with Al, Mg and Fe to form Mg2Si and AlFeMgSi, thereby eliminating or almost eliminating the impurities in the aluminum matrix. The elemental Si of the present invention can avoid the influence of excessive Si addition on the electrical conductivity of the aluminum alloy. The amount of Si added is set to be greater than the amount of Si added in the prior art. On the one hand, Si is beneficial to refine the primary crystal grains. On the other hand, Si reacts with Al, Mg and Fe to form compounds to improve the mechanical properties. It can also avoid the decrease of the electrical conductivity of the aluminum alloy caused by excessive Si. In this way, the amount of Si added in the present invention can be set to be greater than the amount of Si added in the prior art. It can not only break the technical prejudice that the electrical conductivity of the aluminum alloy is affected by excessive Si addition in the prior art, but also improve the electrical conductivity and mechanical properties of the aluminum alloy when more Si is added. It can also avoid the increase in cost caused by excessive addition of high-cost elements and the lack of targeted performance adjustment and complex process caused by the addition of too many types of elements.
[0076] (2) The amount of Cu added can reach 0.6%, which can be greater than the amount of Cu added in the prior art (lower content of Cu has little effect on the electrical conductivity and mechanical properties of aluminum alloys, and higher content of Cu will reduce the electrical conductivity of aluminum alloys. Therefore, the amount of Cu added in the prior art is usually 0.18-0.25%). RE can greatly promote the precipitation of CuAl2 strengthening phase and (CuMg)Al2 strengthening phase, significantly improving the mechanical properties and electrical conductivity of aluminum alloys. Setting the amount of Cu added to be greater than the amount of Cu added in the prior art is beneficial to Cu to improve the electrical conductivity of aluminum alloys. On the other hand, the reaction of Cu with Mg and Al to form a dispersed compound avoids the decrease in the electrical conductivity of the aluminum alloy caused by excessive Cu. In this way, the amount of Cu added in the present invention can be set to be greater than the amount of Cu added in the prior art, which not only breaks the technical prejudice in the prior art that the electrical conductivity of the aluminum alloy is affected by excessive addition of Cu, but also improves the mechanical properties and electrical conductivity of the aluminum alloy when more Cu is added, and avoids the increase in cost caused by excessive addition of high-cost elements and the lack of targeted performance adjustment and complex process caused by the addition of too many types of elements;
[0077] (3) The amount of Mg added can reach 0.7%, which can be greater than the amount of Mg added in the prior art (Mg exists in the alloy mainly in the form of solid solution strengthening. The atomic radius of Mg is quite different from that of aluminum. The higher the content of Mg in the aluminum solid solution, the easier it is to cause lattice distortion and reduce the electrical conductivity of the aluminum alloy. Therefore, the amount of Mg added in the prior art is usually not more than 0.3%). Mg can react with Si and Sn to form Mg2Si and Mg2Sn phases. Some Mg will also be dissolved in CuAl2 phase and AlFeSi phase to form (CuMg)Al2 phase and AlFeSiMg phase, reducing the solubility of alloy elements in the matrix, which can improve the mechanical properties, electrical conductivity and fatigue resistance of the aluminum alloy. The amount of Mg added can be relatively large. Mg can react with Al, Fe, Sn (the amount added can be relatively large), Si (the amount added can be relatively large), Cu (the amount added can be relatively large), and Cu (the amount added can be relatively large). The amount of Mg added can be larger) to react to form a second phase, avoiding excessive Mg solid solution causing lattice distortion of the aluminum alloy. The amount of Mg added is set to be greater than the amount of Mg added in the prior art. On the one hand, it is beneficial to use Mg to improve the mechanical properties of the aluminum alloy. On the other hand, Mg reacts with Si, Cu, Al and Fe to form a second phase to avoid excessive Mg causing a decrease in the mechanical properties and electrical conductivity of the aluminum alloy. In this way, the amount of Mg added in the present invention can be set to be greater than the amount of Mg added in the prior art, which can not only break the technical prejudice in the prior art that excessive addition of Mg affects the mechanical properties and electrical conductivity of the aluminum alloy, but also improve the mechanical properties, electrical conductivity and fatigue resistance of the aluminum alloy when more Mg is added, and can also avoid the increase in cost caused by excessive addition of high-cost elements and the lack of targeted performance adjustment and complex process caused by the addition of too many types of elements;
[0078] (4) The amount of Sn added can reach 0.3%, which can be greater than the amount of Sn added in the prior art (the solid solubility of Sn in the aluminum matrix is extremely low, and excessive Sn will lead to an increase in β(Sn). When β(Sn) is enriched at the grain boundary and solidifies, it will reduce the mechanical properties of the aluminum alloy. Therefore, the amount of Sn added in the prior art is relatively small, usually not more than 0.08%). Sn will react with the remaining Mg to form a spherical dispersed Mg2Sn strengthening phase (Mg reacts first with Si to form a Mg2Si phase, and then reacts with Sn. Sn will also promote the precipitation of the Mg2Si phase), which can reduce Mg The solid solubility of Sn in the aluminum matrix can improve the electrical conductivity of the aluminum alloy. Sn can also generate various high-temperature strengthening phases such as Al9Sn7, Al6Sn5, Al5Sn2, and Al3Sn4 with Al to improve the heat resistance and corrosion resistance of the aluminum alloy. In this way, the amount of Sn added in the present invention can be set to be greater than the amount of Sn added in the prior art, which can not only break the technical prejudice in the prior art that the mechanical properties of the aluminum alloy are affected by excessive addition of Sn, but also improve the heat resistance, corrosion resistance, mechanical properties, and electrical conductivity of the aluminum alloy when more Sn is added;
[0079] (5) RE can refine the alloy structure to improve the mechanical properties of aluminum alloy. RE also forms a rare earth active film on the surface of the iron-containing phase or combines with Al, Fe, Ti and other atoms to form rare earth compounds, effectively reducing the solid solution of harmful element atoms in the aluminum matrix to improve the electrical conductivity and mechanical properties of aluminum alloy. RE can transform the long strip β-Fe phase into the spherical α-Fe phase and modify the elemental Si. RE can also promote dispersion precipitation to further improve the electrical conductivity and mechanical properties of aluminum alloy. In addition, RE can increase the recrystallization temperature of aluminum alloy, thereby improving the heat resistance, strength and plasticity of aluminum alloy.
[0080] (6) The amount of In added can reach 0.2%, which can be greater than the amount of In added in the prior art (excessive In will lead to a decrease in the mechanical properties of the aluminum alloy. Therefore, the amount of In added in the prior art is relatively small, usually not more than 0.1%). In can refine the grains. In can also react with Al to produce AlIn high-temperature strengthening phases. In can react with Cu to generate CuIn high-temperature strengthening phases, which can greatly improve the mechanical properties of the aluminum alloy. The amount of Cu added is sufficient. In this way, the amount of In added in the present invention can be set to be greater than the amount of In added in the prior art. This not only breaks the technical prejudice in the prior art that the mechanical properties of the aluminum alloy are affected by excessive In addition, but also improves the mechanical properties of the aluminum alloy when more In is added.
[0081] The composite addition of In, Sn and RE can refine the grains, stabilize the grain boundary phase, promote the precipitation of the strengthening phase, and improve the high temperature strength, room temperature strength, electrical conductivity, mechanical properties, plasticity and heat resistance of the aluminum alloy. Even if the addition amount of at least one of Mg, Si, Cu, In and Sn is greater than the addition amount of Mg, Si, Cu, In and Sn in the prior art, the Al-Cu-RE rare earth aluminum alloy of the present invention still has better comprehensive performance. The Al-Cu-RE rare earth aluminum alloy of the present invention contains second phases such as Mg2Si, Mg2Sn, Al9Sn7, Al6Sn5, Al5Sn2, Al3Sn4, Al2Cu, AlFeSi, AlFeMgSi, (CuMg)Al2, CuIn, AlIn, etc. Mg2Si, Mg2Sn, Al9Sn7, Al6Sn5, Al5Sn2, Al3Sn4, Al2Cu, CuIn, AlIn, etc. are precipitation strengthening phases, and AlFeSi, AlFeMgSi, (CuMg)Al2, etc. are grain boundary strengthening phases, so that the Al-Cu-RE rare earth aluminum alloy of the present invention has better electrical conductivity and fatigue resistance while maintaining better room temperature strength, high temperature strength, creep resistance and structural stability. Moreover, under the action of In and RE, even if the addition amount of Mg, Si, Cu and In is relatively large, the Al-Cu-RE rare earth aluminum alloy of the present invention can still have better performances. In addition, since the amount of low-cost elements (such as Mg, Si, Cu, In, Sn, etc.) added is increased, and the aluminum alloy can have good comprehensive properties, it is possible to avoid adding too many expensive elements, thereby reducing the cost of the Al-Cu-RE rare earth aluminum alloy of the present invention. In summary, the present invention can obtain an Al-Cu-RE rare earth aluminum alloy for heat-resistant cables with excellent comprehensive properties (especially mechanical properties, heat resistance, corrosion resistance, and electrical conductivity) by using only a small number of low-cost elements on the basis of maintaining low cost and low process complexity.
[0082] The aluminum alloy may further contain at least one of Sb, Sr, Zn, B, Be, Bi, Mo, Cd, Fe, Ca, Ge, Zr, Sc and Co, so that the Al-Cu-RE series rare earth aluminum alloy has better comprehensive properties:
[0083] (1) The amount of Sb added can reach 0.5%, which can be greater than the amount of Sb added in the prior art (the solid solubility of Sb in the aluminum matrix is extremely low, and excessive Sb will reduce the mechanical properties and electrical conductivity of the aluminum alloy. Therefore, the amount of Sb added in the prior art is relatively small, usually not more than 0.3%). Sb will react with the remaining Mg (Mg reacts with Si first, and then with Sb) to generate a spherical dispersed Mg3Sb2 strengthening phase, which can reduce the solid solubility of Mg and Sb in the aluminum matrix, thereby improving the electrical conductivity and mechanical properties of the aluminum alloy. In this way, the amount of Sb added in the present invention can be set to be greater than the amount of Sb added in the prior art, which not only breaks the technical prejudice in the prior art that the mechanical properties and electrical conductivity of the aluminum alloy are affected by excessive addition of Sb, but also improves the mechanical properties and electrical conductivity of the aluminum alloy when more Sb is added;
[0084] (2) Sr can promote the precipitation of precipitated phases and is also a modifier in aluminum alloys. It is adsorbed on the surface of the Si phase during the subsequent nucleation process, inhibiting the growth of the Si phase to improve the hot deformation process performance of the aluminum alloy, and significantly improving the mechanical properties, plasticity and electrical conductivity of the aluminum alloy;
[0085] (3) The amount of Zn added can reach 0.3%, which is greater than the amount of Zn added in the prior art (a small amount of Zn has little effect on the electrical conductivity and mechanical properties of the aluminum alloy. The amount of Zn added in the prior art is usually not more than 0.04%, otherwise it will seriously affect the corrosion resistance, electrical conductivity and mechanical properties of the aluminum alloy). By setting the amount of Zn added to be greater than the amount of Zn added in the prior art, on the one hand, Zn can be used to promote the precipitation of precipitated phases such as Mg2Si and Al2Cu, and eliminate Si single substance. On the other hand, under the action of stress, Zn can form MgZn2 phase with Mg, which plays a precipitation strengthening role. Zn can also generate CaZn and CaAlZn with Al and Ca, so that the aluminum alloy obtains superplasticity. In this way, the amount of Zn added in the present invention can be set to be greater than the amount of Zn added in the prior art, which not only breaks the technical prejudice in the prior art that excessive addition of Zn affects the corrosion resistance, electrical conductivity and mechanical properties of the aluminum alloy, but also improves the mechanical properties and electrical conductivity of the aluminum alloy when more Zn is added;
[0086] (4) Fe can react with Al and Si to form α-Fe2SiAl8 (or Fe3Si2Al 12 ), to avoid the formation of coarse β-FeSiAl3 (or Fe2Si2Al9) phase, α-Fe2SiAl8 (or Fe3Si2Al 12 ) is a cubic structure, which is beneficial to improve the mechanical properties of aluminum alloys. Co can promote the formation of spherical Fe phase. When the addition amount of Co is 0-0.8%, Al3(Fe,Co) phase with smaller particle size can be generated to improve the mechanical properties of aluminum alloys. The generated Al3Fe phase can also be converted into α-Al15 (Fe, Co) 3 Si 2 (which may be in the shape of granules, small flowers or small strips) and has a refining effect on the Al 3 Fe phase, further improving the mechanical properties, heat resistance and plasticity of the aluminum alloy. The present invention sets the mass ratio of Fe to Si to 1:0.1-5, which can ensure that Si fully reacts with Fe and avoid the adverse effect of excessive Si on the electrical conductivity of the aluminum alloy;
[0087] (5) The amount of Cd added can reach 0.3%, which can be greater than the amount of Cd added in the prior art (the amount of Cd added in the prior art is usually not more than 0.1%, otherwise the Cd element will remain in the intergranular form in the form of Cd-rich phase, reducing the plasticity of the aluminum alloy). Cd can refine α-Al and react with Al, Fe and RE in the melt to form various metal compounds such as REAl2Cd3, Fe3Al2Cd, Al3Cd, and Al2Cd3, which can improve the tensile properties of the aluminum alloy. Cd will form a large number of Cd-vacancy clusters in the aging stage, promoting and accelerating the precipitation of CuAl2, Mg3Sb2, Mg3Bi2, Mg2Si, and Mg2Sn phases. Moreover, a large amount of CuAl2 phase precipitates under the action of Cd and RE. When the amount of Cd added is large, sufficient Cd provides nucleation sites for the CuAl2 phase to form (CuCd)Al2, Mg2(SiCdREFe), Mg2(SnCd), Mg3(BiCd)2, AlCuCdMgNi and other strengthening phases are formed, thereby improving the mechanical properties of the aluminum alloy. In addition, a small amount of Cd dispersed in the aluminum matrix can greatly improve the toughness and plasticity of the aluminum alloy. The amount of Cd added is set to be greater than the amount of Cd added in the prior art. On the one hand, it is beneficial for Cd to improve the toughness of the aluminum alloy. On the other hand, Cd reacts with Al, Cu, Sn, Si, Fe and RE to generate compounds to avoid excessive Cd causing a decrease in the plasticity of the aluminum alloy. In this way, the amount of Cd added in the present invention can be set to be greater than the amount of Cd added in the prior art, which not only breaks the technical prejudice in the prior art that the conductive properties of the aluminum alloy are affected by excessive addition of Cd, but also improves the toughness, plasticity, mechanical properties and tensile properties of the aluminum alloy when more Cd is added.
[0088] (6) The amount of Mo added can reach 0.3%, which can be greater than the amount of Mo added in the prior art (the amount of Mo added in the prior art is usually not greater than 0.1%, otherwise the electrical conductivity of the aluminum alloy will be reduced). Mo can refine the grains, and Mo can react with Al to form an AlMo high temperature strengthening phase that can improve the mechanical properties of the aluminum alloy. It can also react with Al and Si to form a Mo(AlSi)2 phase that can improve the corrosion resistance of the aluminum alloy. The amount of Si added is sufficient. In this way, the amount of Mo added in the present invention can be set to be greater than the amount of Mo added in the prior art. This not only breaks the technical prejudice in the prior art that the electrical conductivity of the aluminum alloy is affected by excessive addition of Mo, but also improves the mechanical properties and corrosion resistance of the aluminum alloy when more Mo is added.
[0089] (7) The amount of Sc added can reach 0.3%, which can be greater than the amount of Sc added in the prior art (excessive Sc will lead to excessively large grain size, therefore, the amount of Sc added in the prior art is relatively small, usually not greater than 0.15%). Sc can react with Al to form Al3Sc particles, which can significantly refine the alloy structure, change the size, shape and distribution of the strengthened η phase, thereby improving the mechanical properties, plasticity and high-temperature stability of the aluminum alloy. Sc can also react with Al, Sc and Cu to form AlScCu, Mg2ScSi, Mg2ScSn and Al3ScZr phases, thereby improving the mechanical properties of the aluminum alloy. The amount of Cu added is sufficient, so that the amount of Sc added in the present invention can be set to be greater than the amount of Sc added in the prior art, which not only breaks the technical prejudice in the prior art that the mechanical properties of the aluminum alloy are affected by excessive addition of Sc, but also improves the heat resistance, corrosion resistance, mechanical properties and electrical conductivity of the aluminum alloy when more Sc is added;
[0090] (8) The amount of Zr added can reach 0.3%, which is greater than the amount of Zr added in the prior art (the amount of Zr added in the prior art is usually not more than 0.1%, otherwise the electrical conductivity of the aluminum alloy will drop sharply). Zr can work synergistically with RE to inhibit the recrystallization of the alloy. Zr can also form (Zr, RE)Al3 compounds with rare earth elements such as Er, which promotes the precipitation of β″ phase and makes the β″ phase finer and more dispersed, which can increase the recrystallization temperature and heat resistance of the aluminum alloy. Zr will also promote the precipitation of Mg2Sn, further reducing the concentration of Mg and Sn in the aluminum matrix. The solid solubility of Zr in the present invention is set to be greater than the amount of Zr added in the prior art. On the one hand, Zr is beneficial to improve the mechanical properties and plasticity of the aluminum alloy. On the other hand, Zr reacts with rare earth to form compounds to avoid excessive Zr causing a decrease in the electrical conductivity of the aluminum alloy. In this way, the amount of Zr added in the present invention can be set to be greater than the amount of Zr added in the prior art, which not only breaks the technical prejudice in the prior art that the electrical conductivity of the aluminum alloy is affected by excessive addition of Zr, but also improves the mechanical properties and electrical conductivity of the aluminum alloy when more Zr is added.
[0091] (9) The amount of B added can reach 0.1%, which is greater than the amount of B added in the prior art (too much B will increase the size of the iron-containing phase, causing the aggregation of B grains and reducing the refinement effect, and will also react with strengthening elements to reduce the mechanical properties of the aluminum alloy. The amount of B added in the prior art is usually not more than 0.05%). The amount of B added is set to be greater than the amount of B added in the prior art. In this way, B can not only react with transition metal impurity elements such as Ti, Cr, and Zr to boride and improve the electrical conductivity of the aluminum alloy (this can avoid the influence of excessive Zr addition on the electrical conductivity of the aluminum alloy), but also has a refining effect, improving the mechanical properties and room temperature strength of the aluminum alloy. B can also react with Fe, Al, and Si to form a complex multi-component compound, which can not only further eliminate elemental Si, but also change the morphology of the iron phase (from needle-like to short flake-like, polyhedral or Chinese character-like), so as to improve the mechanical properties and electrical conductivity. In this way, the amount of B added in the present invention can be set to be greater than the amount of B added in the prior art, which can not only break the technical prejudice in the prior art that the mechanical properties of the aluminum alloy are affected by excessive addition of B, but also improve the room temperature strength, mechanical properties and electrical conductivity of the aluminum alloy when more B is added;
[0092] (10) Be can promote the precipitation of Mg2Si, Mg3Bi2, and Mg2Sn phases, reduce Mg loss, avoid casting defects, reduce the generation of oxide impurities, and promote the transformation of the plate-like β intermediate phase into the relatively harmless Chinese character-shaped Be-Fe (Al8Fe2SiBe) phase, and transform the eutectic Si phase from a lamellar phase to a fine phase, thereby increasing the recrystallization temperature of the aluminum alloy and reducing the recrystallization rate of the aluminum alloy, thereby improving the mechanical properties, high temperature strength, room temperature strength, and plasticity of the aluminum alloy;
[0093] (11) The amount of Ge added can reach 0.3%, which can be greater than the amount of Ge added in the prior art (a lower content of Ge has little effect on the electrical conductivity and mechanical properties of the aluminum alloy, while a higher content of Ge will reduce the electrical conductivity and mechanical properties of the aluminum alloy. Therefore, the amount of Ge added in the prior art is usually not more than 0.2%). Ge has a strong binding ability with the quenching vacancies in the α-Al matrix, and is easy to capture the quenching vacancies in the α-Al matrix and form "Ge-vacancy pairs". Ge can form A in the melt. l9Ge7, Al6Ge5, Al5Ge2, Al3Ge4 and other high temperature strengthening phases improve the heat resistance of aluminum alloys. Ge can also refine the precipitation phase, promote the precipitation of precipitation phases (such as Mg2Si and CuAl2, etc.), and replace some Si atoms in the metastable precipitation phase. The Si-Ge phase precipitated at the initial stage of aging provides a nucleation site for the θ phase, increasing the density of the θ phase. The amount of Si added can reach 0.5%, which can react with a large amount of Ge to form Si-Ge phase and provide a nucleation site for the θ phase, thereby improving the mechanical properties and electrical conductivity of the aluminum alloy. In this way, the amount of Ge added in the present invention can be set to be greater than the amount of Ge added in the prior art, which can not only break the technical prejudice in the prior art that the electrical conductivity and mechanical properties of the aluminum alloy are affected by excessive addition of Ge, but also improve the heat resistance, electrical conductivity and mechanical properties of the aluminum alloy when more Ge is added.
[0094] (12) Bi expands during the solidification process, which is beneficial for shrinkage compensation and can also prevent sodium embrittlement. It can react with Mg to form Mg3Bi2 strengthening phase, thereby improving the mechanical properties of aluminum alloys. Ca can refine the eutectic structure and improve the β-Fe phase, thereby improving the alloy's heat treatment properties while increasing its strength. It can also react with Cu and Al to form Al4Ca, Al2Ca3, AlCa2, and AlCaCu strengthening phases, significantly improving the strength, heat resistance, and fatigue resistance of aluminum alloys.
[0095] The composite addition of at least two of Zr, RE, Be, Sn, Ge, Cd, Zn, and Sr promotes the precipitation of strengthening phases such as Mg2Si, Mg3Sb2, Mg3Bi2, Mg2Sn, (CuMg)Al2, and CuAl2; the composite addition of at least two of Zr, RE, Be, B, Sc, Mo, In, Sr, Cd, and Ca refines the grains and replaces the Ti element that causes a sharp drop in conductivity; the composite addition of at least two of Zr, RE, and Be stabilizes the grain boundary phase and improves the high temperature strength, room temperature strength, and heat resistance of the aluminum alloy; the composite addition of at least two of Sc, B, Co, RE, and Ca improves the β-Fe phase and transforms the long strip β-Fe The phase is transformed into a spherical α-Fe phase, and the elemental Si is modified; the composite of B and Sr can modify the aluminum matrix and Mg2Si phase, so that the distribution of elements such as Ti, V, Cr to the grain boundary is reduced, and reacts with them to form massive borides, so that the solid solution elements such as Ti, V, Cr are transformed into a precipitation state, which weakens the lattice distortion of Al and increases the conductivity; the addition amount of at least one of Mg, Si, Cu, Sc, In, Zr, Ge, Sn, Sb, B, Cd and Zn is set to be greater than the addition amount of Mg, Si, Cu, Sc, In, Zr, Ge, Sn, Sb, B, Cd and Zn in the prior art, so as to avoid adding too many expensive elements, and at the same time obtain A l9A lMo, CuIn, AlIn, AlScCu, Mg2ScSi, Mg2ScSn, Mg3(ScBi)2, Mg3(ScSb)2, Mg3Bi2, MgZn2, CaZn, CaAlZn, AlCaCu, Al9Sn7, Al6Sn5, Al5Sn2, Al3Sn4, α-Al 15 (Fe,Co)3Si2, Al3(Fe,Co), Mg2Sn, Mg3Sb2, Mg2Si, Al2Cu, Al3(Zr,RE), AlFeMgSiNi, FeNiAl9, AlFeSi, Second phases such as AlFeMgSi, (CuMg)Al2, AlFeSiNi, Be-Fe(Al8Fe2SiBe), Al4Ca, Al2Ca3, AlCa2, AlCaCu, Al3ScZr, A l9 Ge7, Al6Ge5, Al5Ge2, Al3Ge4, Al3Cd, Al2Cd3, AlMo, CuIn, AlIn, Al3Sc, Mg3Bi2, MgZn2, CaZn, Al9Sn7, Al6Sn5, Al5Sn2, Al3Sn4, Mg2Sn, AlCaCu, Mg3Sb2, Mg2Si, Al2Cu, Al4Ca, Al2Ca3, AlCa2, etc. are precipitation strengthening phases, (CuCd)Al2, Mg2(SiCdREFe), Mg2(SnCd), Mg3(BiCd)2, AlCuCdMgNi, Mo(AlSi)2, AlScCu, Mg2ScSi, Mg2ScSn, Mg3(ScBi)2, Mg3(ScSb)2, REAl2Cd3, Fe3Al2Cd, α-Al 15 (Fe,Co)3Si2, Al3(Fe,Co), Al3(Zr,RE), AlFeMgSiNi, FeNiAl9, AlFeSi, AlFeMgSi, (CuMg)Al2, AlFeSiNi, Be-Fe(Al8Fe2SiBe), CaAlZn, AlCaCu, Al3ScZr, etc. are grain boundary strengthening phases, which make Al-Cu-RE rare earth aluminum alloys have better comprehensive properties, especially mechanical properties, heat resistance, corrosion resistance, and electrical conductivity.
[0096] The present invention also provides a method for preparing an Al-Cu-RE series rare earth aluminum alloy, comprising the following steps:
[0097] Melting: Heat the aluminum source (such as aluminum ingot) to 720-780℃ to obtain aluminum liquid, add Cu, Mg, Si, RE, In, Sn to the aluminum liquid for heating and melting, stir evenly, refine, degas and slag, stand at 700-750℃ for 10-30min, and after obtaining the alloy liquid, keep it warm and stand it for composition and content detection;
[0098] Continuous casting and rolling: After the composition and content are tested to be qualified, the alloy liquid after degassing and slagging treatment is continuously cast and rolled to obtain aluminum alloy rods;
[0099] Drawing treatment: drawing the aluminum alloy rod to obtain an aluminum alloy wire;
[0100] Twisting process: Twisting aluminum alloy wire with high elastic wire to form aluminum alloy conductor; and
[0101] Aging treatment: Aging treatment is performed on the aluminum alloy conductor, and cooling is performed to obtain the Al-Cu-RE rare earth aluminum alloy. The Al-Cu-RE rare earth aluminum alloy contains 0.01-0.6% Cu by mass, 0.001-0.2% RE by mass, 0-0.7% Mg by mass, 0-0.3% Si by mass, 0-0.2% In by mass, 0-0.3% Sn by mass, Al and unavoidable impurities.
[0102] It is understandable that when the content of each component in the alloy liquid after degassing and slag removal treatment meets the standard, subsequent treatments such as continuous casting and rolling are carried out. Wherein, the aluminum alloy contains 0.01-0.6% Cu by mass percentage, 0.001-0.2% RE by mass percentage, 0-0.7% Mg by mass percentage, 0-0.3% Si by mass percentage, 0-0.2% In by mass percentage, 0-0.3% Sn by mass percentage, and Al and unavoidable impurities. When the composition and content are unqualified, the corresponding elements can be added to adjust until the composition and content are qualified.
[0103] In one embodiment, the mass percentage content of Cu may be 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, or 0.6%; the mass percentage content of Mg may be 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, or 0.6%. 33%, 0.34%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, or 0.7%; the mass percentage content of Si can be 0.001%, 0.005%, 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.21%, 0.25%, or 0.3%; the mass percentage content of RE can be 0.001%, 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05% , 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, or 0.2%; the mass percentage content of In can be 0.001%, 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0. The mass percentage content of Sn can be 0.001%, 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.2%, 0.25%, or 0.3%.
[0104] The mass ratio of Mg, Sn and Si is 1-20:0.5-5:1. Specifically, the mass ratio of Mg, Sn and Si is 1:0.5:1, 1:1:1, 1:1.5:1, 1:2:1, 1:2.5:1, 1:3:1, 1:4:1, 1:4.5:1, 1:5:1, 5:0.5:1, 5:1:1, 5:1.5:1, 5:2:1, 5:2.5:1, 5:3:1, 5:4:1, 5:4.5:1, 5:5:1, 10:0.5:1, 10:1:1, 10:1.5:1, 10:2:1, 10:2 .5:1, 10:3:1, 10:4:1, 10:4.5:1, 10:5:1, 15:0.5:1, 15:1:1, 15:1.5:1, 15:2:1, 15:2.5:1, 15:3:1, 15:4:1, 15:4.5:1, 15:5:1, 20:0.5:1, 20:1:1, 20:1.5:1, 20:2:1, 20:2.5:1, 20:3:1, 20:4:1, 20:4.5:1, or 20:5:1.
[0105] The mass ratio of Mg to Si is 0.2-40: 1. Specifically, the mass ratio of Mg to Si is 0.2: 1, 0.5: 1, 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, 20: 1, 30: 1, or 40: 1. Within the range of the mass ratio, as the mass ratio of Mg / Si increases, the conductive strength gradually increases.
[0106] The mass ratio of Cu to Si may be 0.5-30: 1. Specifically, the mass ratio of Cu to Si is 0.5: 1, 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, 20: 1, 25: 1, 30: 1, 35: 1, or 40: 1. Within the range of this mass ratio, as the mass ratio of Cu / Si increases, the tensile strength gradually increases.
[0107] The mass ratio of Mg to In is 0.3-40: 1. Specifically, the mass ratio of Mg to In is 0.3: 1, 0.5: 1, 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, 20: 1, 25: 1, 30: 1, 35: 1, or 40: 1. Within the range of the mass ratio, as the mass ratio of Mg / In increases, the conductive strength gradually increases.
[0108] The mass ratio of Cu to In is 0.3-40:1. Specifically, the mass ratio of Cu to In is 0.3:1, 0.5:1, 1:
[0109] 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, 20: 1, 25: 1, 30: 1, 35: 1, or 40: 1. Within the range of this mass ratio, as the mass ratio of Cu / In increases, the tensile strength gradually increases.
[0110] RE is at least one of La, Ce, Pr, Nd, Er, Sm, Y, and Gd.
[0111] The mass percentage content of the impurities is no more than 0.15%, and the mass percentage content of a single impurity is less than 0.05%.
[0112] In one embodiment, the casting temperature is 680-750°C, and the rolling temperature is 450-550°C.
[0113] In one embodiment, the drawing process may be cold drawing. During cold drawing, the aluminum alloy rod is drawn into an aluminum alloy wire within a predetermined diameter range, and the elongation coefficient of each cold drawing is controlled to be 0.5-2. After each cold drawing, the temperature is raised to 250-350° C., kept for 5-20 hours, and a secondary heat treatment is performed to obtain the aluminum alloy wire.
[0114] In one embodiment, the aging treatment is a bipolar aging treatment, and the bipolar aging treatment includes the following steps: firstly, a low-temperature aging treatment is performed at a temperature of 100-150°C for a time of 1-150h; and then a high-temperature aging treatment is performed at a temperature of 150-250°C for a time of 1-100h. The bipolar aging treatment can precipitate the solid solution elements in the aluminum alloy as much as possible to improve the mechanical properties and electrical conductivity of the aluminum alloy. The temperature of the high-temperature aging treatment can be greater than that of the low-temperature aging treatment. The temperature of the low-temperature aging treatment can be 100°C, 110°C, 120°C, 130°C, 140°C, or 150°C. The temperature of the high-temperature aging treatment can be 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, or 250°C. The time of low temperature aging treatment may be 1h, 10h, 20h, 30h, 40h, 50h, 60h, 70h, 80h, 90h, 100h, 110h, 120h, 130h, 140h, or 150h. The time of high temperature aging treatment may be 1h, 10h, 20h, 30h, 40h, 50h, 60h, 70h, 80h, 90h, or 100h. The time of high temperature aging treatment may not be greater than the time of low temperature aging treatment. The temperature of high temperature aging treatment may be 1.2-2.5 times the temperature of low temperature aging treatment, preferably 1.5-2 times. The time of low temperature aging treatment may be 1.1-50 times the time of high temperature aging treatment, preferably 5-40 times, preferably 10-20 times.
[0115] In one embodiment, the temperature of the refining treatment is 690-750°C and the time is 10-20 minutes. The refining agent of the refining treatment may include the following raw materials in parts by weight: 60-70 parts of KF, 50-60 parts of NaCl, 40-60 parts of LiCl, 20-25 parts of cryolite, 10-25 parts of AIF3, 10-15 parts of CaF2, 5-10 parts of light calcium carbonate, 15-20 parts of graphite powder, 10-20 parts of talc, 20-30 parts of MgCl2, and 10-30 parts of rare earth acid salt. The rare earth acid salt may be one of the chlorides, fluorides, and nitric acid compounds of light rare earths, or a combination thereof. The rare earth acid salt may be one of the chlorides, fluorides, and nitric acid compounds of heavy rare earths, or a combination thereof. The mass ratio of the refining agent to the alloy liquid is 0.0013-0.0018:1.
[0116] In one embodiment, at least one of Sb, Sr, Sc, Zn, B, Be, Bi, Mo, Cd, Fe, Ca, Ge, Zr, and Co may be added to the aluminum liquid.
[0117] In one embodiment, Cu, Mg, Si, RE, In, Sc, Sb, Sr, Zn, B, Be, Bi, Mo, Cd, Fe, Ca, Ge, Zr, and Co are added in the form of single elements and / or aluminum master alloys.
[0118] The mass percentage content of Sb may be 0-0.5%. The mass percentage content of Sr may be 0-0.2%. The mass percentage content of Sc may be 0-0.3%. The mass percentage content of Zn may be 0-0.3%. The mass percentage content of B may be 0-0.1%. The mass percentage content of Be may be 0-0.1%. The mass percentage content of Bi may be 0-0.3%. The mass percentage content of Mo may be 0-0.3%. The mass percentage content of Cd may be 0-0.3%. The mass percentage content of Co may be 0-0.8%. The mass percentage content of Ca may be 0-0.5%. The mass percentage content of Ge may be 0-0.3%. The mass percentage content of Zr may be 0-0.3%. The mass percentage content of Fe may be 0-0.3%.
[0119] The mass ratio of Mg to Fe can be 0.2-20:1, specifically 0.2:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, or 20:1.
[0120] The mass ratio of Sc to Fe can be 0.1-10:1, specifically 0.1:1, 0.2:1, 0.5:1, 1:1, 2:
[0121] 1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1.
[0122] The mass ratio of Si to Fe can be 0.1-5:1, specifically 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 2:1, 3:1, 4:1, or 5:1.
[0123] The mass ratio of Mg to Sc is 0.1-20: 1. Specifically, the mass ratio of Mg to Sc is 0.1: 1, 0.2: 1, 0.5: 1, 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, or 20: 1. Within the range of the mass ratio, as the mass ratio of Mg / Sc increases, the conductive strength gradually increases.
[0124] The mass ratio of Cu to Sc may be 1-30: 1. Specifically, the mass ratio of Cu to Sc is 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, 20: 1, 25: 1, or 30: 1. Within the range of this mass ratio, as the mass ratio of Cu / Sc increases, the tensile strength gradually increases.
[0125] The mass ratio of Sc to Zr is 0.5-2.5:1, and can be specifically 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 2:1, or 2.5:1.
[0126] The mass ratio of In to B is 0.1-10:1, for example, 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1.
[0127] The mass ratio of Sc, In, and B is 0.1-15:0.1-10:1, preferably 1-10:1-5:1. The mass ratio of Sc, In, and B can be specifically 0.1:0.1:1, 0.5:0.1:1, 1:0.1:1, 5:0.1:1, 10:0.1:1, 15:0.1:1, 0.1:1:1, 0.5:1:1, 1:1:1, 5:1:1, 10:1:1, 15:1:1, 0.1:5:1, 0.5:5:1, 1:5:1, 5:5:1, 10:5:1, 15:5:1, 0.1:10:1, 0.5:10:1, 1:10:1, 5:10:1, 10:10:1, or 15:10:1.
[0128] In the technical solution of the present invention, Cu, Mg, Si, RE, Sn, and In are added to the aluminum liquid, and after heating and smelting, continuous casting and rolling, drawing treatment, stranding treatment, and aging treatment are carried out to obtain Al-Cu-RE rare earth aluminum alloy. The Al-Cu-RE rare earth aluminum alloy contains 0.01-0.6% Cu by mass percentage, 0.001-0.2% RE by mass percentage, 0-0.7% Mg by mass percentage, 0-0.3% Si by mass percentage, 0-0.2% In by mass percentage, and 0-0.3% Sn by mass percentage. When the above elements are added to the aluminum matrix alone, the improvement of the electrical conductivity and mechanical properties of aluminum is limited, and even has a negative effect on the electrical conductivity and mechanical properties of aluminum. The present invention adds the above elements to the aluminum matrix together, and the above elements interact and influence each other, which can reduce the solid solubility of each other in the aluminum matrix, so as to reduce the adverse effects of certain elements on electrical conductivity and improve electrical conductivity. The elements will also be dissolved into other precipitated phases and second phases to form strengthening phases, thereby significantly improving the comprehensive performance of the aluminum alloy. The Al-Cu-RE series rare earth aluminum alloy uses a small number of elements and is inexpensive. Although RE and Sc are slightly more expensive, they are used in small amounts and have little impact on the cost of the Al-Cu-RE series rare earth aluminum alloy. In addition, RE and Sc composites have mechanical properties and electrical conductivity that other elements cannot match. The coordination of each element can also promote the precipitation volume fraction of the strengthening phase to reduce the total amount of elements added to the aluminum matrix. Generally, in a soft heat-resistant cable, the amount of alloying elements added is inversely proportional to the electrical conductivity and elongation, and is proportional to the tensile strength and yield strength. In the soft state, to ensure that the electrical conductivity reaches the national standard value (greater than 61% IACS), the total amount of elements added to the aluminum alloy for cables does not exceed 1.0wt%; to ensure that the tensile strength is greater than 185MPa, the total amount of elements added to the aluminum alloy for cables generally exceeds 1.0wt%, however, the electrical conductivity will definitely be lower than the national standard value (greater than 61% IACS); while the present invention, under the premise of ensuring mechanical properties and electrical conductivity, when the total amount of elements added to the aluminum alloy is less than 1.0wt%, better comprehensive performance can be achieved (specifically, the tensile strength of the Al-Cu-RE rare earth aluminum alloy is greater than the tensile strength of the hard alloy, the elongation of the Al-Cu-RE rare earth aluminum alloy is greater than the elongation of the soft alloy, and the electrical conductivity is greater than 61% IACS), thereby reducing the cost of the Al-Cu-RE rare earth aluminum alloy. In summary, the present invention can obtain Al-Cu-RE rare earth aluminum alloy for heat-resistant cables with excellent comprehensive properties (especially mechanical properties, heat resistance, corrosion resistance, and electrical conductivity) by using only a small number of low-priced elements while maintaining low cost and low process complexity.
[0129] The present invention also provides a heat-resistant cable, comprising a core and an insulating layer covering the core, wherein the core is made of the Al-Cu-RE rare earth aluminum alloy. The heat-resistant cable may also include other components. In one embodiment, the heat-resistant cable may also include an inner shielding layer disposed between the core and the insulating layer, an outer shielding layer covering the insulating layer, and a protective layer covering the core and the outer shielding layer.
[0130] Since the heat-resistant cable adopts all the technical solutions of all the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0131] Examples and Comparative Examples
[0132] Please refer to Table 1 for the components and contents of the aluminum alloys of Examples 1 to 7 and Comparative Examples 1 to 4, and please refer to Table 2 for the performance test results.
[0133] Table 1 Composition and content of aluminum alloys of Examples 1 to 7 and Comparative Examples 1 to 4
[0134]
[0135]
[0136] To simplify the description, the comparative examples and examples do not show the contents of trace elements such as impurities.
[0137] The conductivity of the aluminum alloys of Examples 1 to 7 and Comparative Examples 1 to 4 was tested using a digital DC bridge meter of model QJ57 produced by Shanghai Zhengyuan Electric Technology Co., Ltd. The sample size was Φ2.5mm×1000mm. During the test, the temperature was controlled at 20±0.1°C. Three samples were tested under the same condition and the average value was taken.
[0138] At room temperature, according to the test requirements of GB4909 "Bare Wire Tensile Test", the mechanical properties of the aluminum alloys of Examples 1 to 7 and Comparative Examples 1 to 4 were tested using a domestic CSS-44100 electronic universal tensile machine. The tensile force of the electronic universal tensile machine was 2 kN, the tensile speed was 2 mm / min, and three samples were tested under the same condition to take the average value.
[0139] The heat resistance (strength residual rate) of the aluminum alloys of Examples 1 to 7 and Comparative Examples 1 to 4 was tested using a domestic JCT-1 electric high-temperature drying oven with a temperature fluctuation of ±1°C. The annealing temperature was 230°C, the holding time was 1h, and three samples were tested under the same condition to take the average value.
[0140] Table 2 Performance test results of aluminum alloys of Examples 1 to 7 and Comparative Examples 1 to 4
[0141]
[0142]
[0143] The tensile strength, elongation, electrical conductivity and heat resistance of the Al-Cu-RE rare earth aluminum alloys of Examples 1 to 7 are significantly greater than those of the Al-Cu-RE rare earth aluminum alloys of Comparative Examples 1 to 4, indicating that the Al-Cu-RE rare earth aluminum alloys of the present invention have better performances.
[0144] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or direct / indirect application in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. An Al-Cu-RE rare earth aluminum alloy, characterized in that: The Al-Cu-RE rare earth aluminum alloy is composed of the following elements: 0.01-0.6% Cu by mass, 0.001-0.2% RE by mass, 0.01-0.7% Mg by mass, 0.001-0.3% Si by mass, 0.001-0.2% In by mass, 0.01-0.8% Co by mass, 0.001-0.3% Cd by mass, 0.001-0.3% Sn by mass, and Al, wherein the mass ratio of Cu to In is 0.3-40:
1. The preparation method of the Al-Cu-RE rare earth aluminum alloy comprises the following steps: The aluminum source is subjected to a first heating treatment to obtain aluminum liquid; Adding Cu, Mg, Si, RE, In, Co, Cd, and Sn to the aluminum liquid, performing a second heating treatment, and obtaining an alloy liquid; Refining and slagging the alloy liquid, and testing its composition and content; After the composition and content are tested to be qualified, the alloy liquid after the refining treatment and slag removal treatment is subjected to continuous casting, continuous rolling and drawing treatment to obtain aluminum alloy wire; and The aluminum alloy wire is subjected to aging treatment to obtain the Al-Cu-RE series rare earth aluminum alloy.
2. The Al-Cu-RE rare earth aluminum alloy according to claim 1, characterized in that: Meet at least one of the following conditions: The mass ratio of Mg to Si is 0.2-40:1; The mass ratio of Cu to Si is 0.5-30:1; The mass ratio of Mg to In is 0.3-40:1; The mass ratio of Mg, Sn, and Si is 1-20:0.5-5:1; RE is at least one of La, Ce, Pr, Nd, Er, Sm, Y, and Gd.
3. The Al-Cu-RE rare earth aluminum alloy according to claim 1, characterized in that: Meet at least one of the following conditions: The Al-Cu-RE rare earth aluminum alloy also contains Sb with a mass percentage of 0.05-0.5%; The Al-Cu-RE rare earth aluminum alloy further contains Sr in an amount of 0.001-0.2% by mass; The Al-Cu-RE rare earth aluminum alloy also contains 0.001-0.3% by mass of Zn; The Al-Cu-RE rare earth aluminum alloy further contains 0.001-0.1% Be by mass percentage; The Al-Cu-RE rare earth aluminum alloy further contains Bi in an amount of 0.001-0.3% by mass; The Al-Cu-RE rare earth aluminum alloy also contains 0.001-0.3% by mass of Mo; The Al-Cu-RE rare earth aluminum alloy further contains 0.05-0.5% by mass of Ca; The Al-Cu-RE rare earth aluminum alloy further contains Ge in an amount of 0.001-0.3% by mass.
4. The Al-Cu-RE rare earth aluminum alloy according to any one of claims 1 to 3, characterized in that: The Al-Cu-RE rare earth aluminum alloy further contains 0.001-0.15% Fe by mass, wherein the mass ratio of Mg to Fe is 0.2-20:1, and the mass ratio of Si to Fe is 0.1-5:
1.
5. The Al-Cu-RE rare earth aluminum alloy according to any one of claims 1 to 3, characterized in that: The Al-Cu-RE rare earth aluminum alloy further contains 0.001-0.1% by mass of B, wherein the mass ratio of In to B is 0.1-10:
1.
6. The Al-Cu-RE rare earth aluminum alloy according to any one of claims 1 to 3, characterized in that: The Al-Cu-RE rare earth aluminum alloy further contains Sc with a mass percentage of 0.001-0.3% and Zr with a mass percentage of 0.001-0.3%, the mass ratio of Mg to Sc is 0.2-30:1, the mass ratio of Cu to Sc is 1-30:1, and the mass ratio of Sc to Zr is 0.5-2.5:
1.
7. The Al-Cu-RE rare earth aluminum alloy according to any one of claims 1 to 3, characterized in that: The Al-Cu-RE rare earth aluminum alloy further contains 0.001-0.1% by mass of B, 0.001-0.15% by mass of Fe, and 0.001-0.3% by mass of Sc, wherein the mass ratio of Sc to Fe is 0.01-10:1, and the mass ratio of Sc, In, and B is 0.1-15:0.1-10:
1.
8. A method for preparing the Al-Cu-RE rare earth aluminum alloy according to any one of claims 1 to 7, comprising the following steps: The aluminum source is subjected to a first heating treatment to obtain aluminum liquid; Adding Cu, Mg, Si, RE, In, Co, Cd, and Sn to the aluminum liquid, performing a second heating treatment, and obtaining an alloy liquid; Refining and slagging the alloy liquid, and testing its composition and content; After the composition and content are tested to be qualified, the alloy liquid after the refining treatment and slag removal treatment is subjected to continuous casting, continuous rolling and drawing treatment to obtain aluminum alloy wire; and The aluminum alloy wire is subjected to aging treatment to obtain an Al-Cu-RE series rare earth aluminum alloy, wherein the Al-Cu-RE series rare earth aluminum alloy is composed of the following elements: 0.01-0.6% Cu by mass, 0.001-0.2% RE by mass, 0.01-0.7% Mg by mass, 0.001-0.3% Si by mass, 0.001-0.2% In by mass, 0.01-0.8% Co by mass, 0.001-0.3% Cd by mass, 0.001-0.3% Sn by mass, and Al, and the mass ratio of Cu to In is 0.3-40:
1.
9. The method for preparing the Al-Cu-RE rare earth aluminum alloy according to claim 8, characterized in that: Meet at least one of the following conditions: The preparation method of the Al-Cu-RE series rare earth aluminum alloy further comprises the step of adding at least one of Sb, Sr, Zn, B, Be, Bi, Mo, Fe, Ca, Ge, Zr, and Sc to the aluminum liquid; The aging treatment is a bipolar aging treatment, which includes the following steps: firstly performing a low-temperature aging treatment at a temperature of 140-150° C. for 20-150 hours; and then performing a high-temperature aging treatment at a temperature of 200-250° C. for 20-100 hours.
10. A heat-resistant cable, characterized in that: It comprises a wire core and an insulating layer covering the wire core, and the material of the wire core is the Al-Cu-RE series rare earth aluminum alloy as described in any one of claims 1 to 7.
Citation Information
Patent Citations
Al-Fe-Ba-RE aluminum alloy, its preparation method, and power cables
CN102978448B
Heat-resistant aluminum-alloy conductor material for cables and manufacture method thereof
CN101948971A
Super-soft aluminum alloy conductor and preparation method thereof
CN101974709A
An aluminum alloy material and its preparation method
CN102268575A
High-conductivity and heat-proof medium-strength aluminum alloy wire and production technology thereof
CN109234579A